If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12n+11=-10n+37
We move all terms to the left:
-12n+11-(-10n+37)=0
We get rid of parentheses
-12n+10n-37+11=0
We add all the numbers together, and all the variables
-2n-26=0
We move all terms containing n to the left, all other terms to the right
-2n=26
n=26/-2
n=-13
| 1.50m•5=15.50 | | x/6-1.5=4 | | 15a=-2 | | -12n+11=-10+37 | | x^2+154x+304=0 | | -5w-10=2-(w+2)+1 | | a/3+8=9 | | 3x+10=8x-12 | | 8+13x=4(12x+37)+x | | 1/2n-19=-14 | | 6x-5/4=8 | | 2/5(5x+5x)1=20 | | -3(4h-10)=1/2(-24+60) | | -111=37d | | 2/55x-x5=20 | | 2^4x-3=8^2x-5 | | 5a^2+40a+80=0 | | 4m-9=2m+16 | | 4x+6=8x-3 | | 2x3+-3x2+.5=0 | | 355x=5x | | 2/5(5x-5x)=20 | | 15+5c=13+4c | | 12-x=0-x | | (x-11)/x=0 | | 5x-4+5x=16 | | 3x-5(x-5)=-3+4x-20 | | 5p+.50=11.50 | | -3(2x-6)=10x-5 | | 6(n-2)-11n=0 | | 44/9-311/9=44/9y | | −3x=6+(−1) |